INTRAFAMILY VIOLENCE WITNESSED AND EXPERIENCED BY SCHOOL ADOLESCENTS - Lima, Carla Cristina Oliveira de Jesus; Martins, Ridalva Dias; Gomes, Nadirlene Pereira; Cruz, Moniky Araújo da; Gomes, Nadjane Rebouças; Silva, Keile Kemyly Assis da; Corrêa, Ritieli Mallagutti (Cogitare Enfermagem, 2022)
Objective: to identify the forms, expressions, and the practitioners of intrafamily violence witnessed and/or experienced by adolescent students. Method: cross-sectional, descriptive study conducted in a public school in Salvador, Bahia - Brazil, with 230 adolescent students in November 2018. The database was archived using the Microsoft Excel program, and frequencies were measured using the chi-square test. Results: the study shows that 121 (52.6%) adolescents experience intra-family violence in psychological, physical, and sexual forms. Among the types of violence experienced by the adolescents, psychological (49.5%) and physical (55.7%) violence were most perpetrated by father/mother and sexual (75.9%) violence was commonly reported by other relatives. Conclusion: the findings of this study contribute to give visibility to the forms of expression of intrafamily violence experienced and witnessed by the child and youth population.